Lupine and horse-bean seeds in diets of growing and fattening sheep - El Maadoudi E.H. (Nutrition and feeding strategies of sheep and goats under harsh climates, 2004)
Crude protein (CP) deficiency in ruminant diets is a major constraint in Morocco. Utilization of lupine seeds could be a way to upgrade their nutritional value. This study was conducted to evaluate the incorporation of Lupinus albus multolupa seeds on the diet, replacing horse-bean. Three iso-nitrogenous diets were used, containing different levels of lupine, oat-vetch hay and different proportions of barley. Each treatment included 8 lambs, fed individually during 105 days with 15 for adaptation. In vivo digestibility and nitrogen balance were measured in three lambs per treatment. There was no significant effect on weight gain, intake, feed efficiency, carcass yield. Neither in dry matter, organic matter and CP digestibility. There was significant effect on neutral detergent fibre and acid detergent fibre digestibility. Incorporation of lupine did not affect the nutritional value of diets but it gave a profit of US dollars 0.2 per kg of weight gain compared to horse-bean.
9. Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2001/11/08-10, Hammamet (Tunisia)